1, 2‐trans‐Stereoselective 7‐O‐Glycosylation of Flavonoids with Unprotected Pyranoses by Mitsunobu Reaction. Issue 9 (23rd March 2022) - Shi, Hailong; Yang, Jian; Cheng, Yao; Yang, Jinlian; Lu, Xiaoxia; Ma, Xiaofeng
Abstract: The glycosylation of protecting‐group‐free pyranoses with flavonoids to generate flavonoid O ‐glycosides under Mitsunobu conditions was reported. The methodology allows to prepare a wide range of natural 7‐flavonoid O ‐glycosides and their derivatives from commercially available chemicals in good to excellent yields with exclusive 1, 2‐ trans ‐stereoselectivity regardless the anomeric configuration of employed pyranoses. The highly regioselective glycosylation was also achieved among different types of hydroxyl groups on the glycosyl acceptors. Abstract : The Mitsunobu reaction was employed to enable the synthesis of flavonoid O ‐glycosides under mild and neutral conditions. The protocol afforded a wide range of flavonoids including natural products and their analogues in good to excellent yields with high 1, 2 ‐trans ‐stereoselectivity. The methodology was also applicable to highly regioselective glycosylation among different hydroxyl groups on the glycosyl acceptor.